Symbol, Sacrality, And Sociality: The Social Construction of The Meaning of Wedding Rings in Christian and Muslim Customary Communities in Maluku - Tutkey, Lusanra Jacqueline; Koritelu, Paulus; Matakena, Fransina (Baileo: Jurnal Sosial Humaniora, 2025)
This article examines the social construction of the meaning of wedding rings within two culturally and religiously distinct customary communities in Maluku: Negeri Amahusu (predominantly Christian) and Negeri Batu Merah (predominantly Muslim). The primary aim is to explore how wedding rings—as marital symbols—are interpreted differently within each community’s social, religious, and cultural context. Employing a qualitative approach and grounded in the social construction theory of Peter L. Berger and Thomas Luckmann, this study draws on in-depth interviews, participant observation, and document analysis conducted in both communities. The findings reveal that the wedding ring is not merely a romantic or legal symbol but is regarded as a sacred object embodying religious values, communal morals, and social identity—shaped and transmitted through family practices, religious narratives, and intercultural interactions. The novelty of this study lies in its cross-community reading of a shared symbol, highlighting how marriage symbols serve as intersubjective mediums for transmitting collective values. The study concludes that cultural symbols like wedding rings play a crucial role in fostering social cohesion and promoting interfaith understanding in multicultural societies. It recommends strengthening intercultural studies in the social sciences and humanities to deepen insights into symbolic dynamics within pluralistic communities.